Expanding the Clinico-Genetic Spectrum of Myofibrillar Myopathy: Experience From a Chinese Neuromuscular Center - Luo, Yue-Bei; Peng, Yuyao; Lu, Yuling; Li, Qiuxiang; Duan, Huiqian; Bi, Fangfang; Yang, Huan (Frontiers in Neurology, 2020)
Background: Myofibrillar myopathy is a group of hereditary neuromuscular disorders characterized by dissolution of myofibrils and abnormal intracellular accumulation of Z disc-related proteins. We aimed to characterize the clinical, physiological, pathohistological and genetic features of Chinese myofibrillar myopathy patients from a single neuromuscular center. Methods: a total of 18 patients were enrolled. Demographic and clinical data were collected. Laboratory investigations, electromyography and cardiac evaluation was performed. Routine and immunohistochemistry stainings against desmin, αB-crystallin and BAG3 of muscle specimen were carried out. Finally, next-generation sequencing panel array for genes associated with hereditary neuromuscular disorders were performed. Results: twelve pathogenic variants in DES, BAG3, FLNC, FHL1 and TTN were identified, of which 7 were novel mutations. The novel DES c.1256C>T substitution is a high frequency mutation. The combined recessively/dominantly transmitted c.19993G>T and c.107545delG mutations in TTN gene cause a limb girdle muscular dystrophy phenotype with the classical myofibrillar myopathy histological changes. Conclusions: we report for the first time that hereditary myopathy with early respiratory failure patient can have peripheral nerve and severe spine involvement. The mutation in Ig-like domain 16 of FLNC is associated with the limb girdle type of filaminopathy, and the mutation in Ig-like domain 18 with distal myopathy type. These findings expand the phenotypic and genotypic correlation spectrum of myofibrillar myopathy.